Air Deployed Oceanographic Mooring (ADOM). - EG AND G WASHINGTON ANALYTICAL SERVICES CENTER INC ROCKVILLE MD (1980)
This document describes accomplishments in the Air Deployed Oceanographic Mooring (ADOM) program during 1979. For the open ocean ADOM, progress in 1979 was marked by two major tests of subassemblies of the ADOM system, as well as several component tests. The anchor subassembly was drop tested from the R/V OCEANUS in late September in the North Atlantic Ocean. In November, the decelerator subassembly was proven in a series of air drops from a C-130 aircraft near Key West, Florida, using a full scale model weighted to duplicate the ballistic characteristics of ADOM. The Arctic ADOM program is addressing the problems of air dropping an oceanographic mooring onto the ice, penetrating the ice with a drill, and deploying a sensor string. In 1979, the effort produced a system design and preliminary ice penetration hardware. The design and hardware show a great potential for success in meeting Arctic ADOM program goals.